2017
DOI: 10.1039/c6en00589f
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of iron–organic matter nano-aggregate networks through a combination of SAXS/SANS and XAS analyses: impact on As binding

Abstract: The present work highlights the fractal organization of iron nanoparticles associated with organic matter and the impact of the aggregate structure on arsenic adsorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 56 publications
7
69
0
Order By: Relevance
“…This model of Fe oxy-hydroxide occlusion in OM is well illustrated in several studies (Du et al, 2018;Eusterhues et al, 2014;Kleber et al, 2015). The density of SROFe-OM aggregates (Eusterhues et al, 2008;Guenet et al, 2017;Mikutta, 2011;Mikutta et al, 2008) together with the size of the ferrihydrite crystallites and their crystallinity (Eusterhues et al, 2008;Mikutta, 2011;Mikutta et al, 2010;Schwertmann et al, 2005) has been shown to vary with the experimental conditions. In a limited number of studies, Fe-coprecipitates were reported to be formed by Fe-oligomers, without reaching the polymerization level of ferrihydrite (Angelico et al, 2014;Mikutta, 2011;Vilgé et al, 1999b).…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…This model of Fe oxy-hydroxide occlusion in OM is well illustrated in several studies (Du et al, 2018;Eusterhues et al, 2014;Kleber et al, 2015). The density of SROFe-OM aggregates (Eusterhues et al, 2008;Guenet et al, 2017;Mikutta, 2011;Mikutta et al, 2008) together with the size of the ferrihydrite crystallites and their crystallinity (Eusterhues et al, 2008;Mikutta, 2011;Mikutta et al, 2010;Schwertmann et al, 2005) has been shown to vary with the experimental conditions. In a limited number of studies, Fe-coprecipitates were reported to be formed by Fe-oligomers, without reaching the polymerization level of ferrihydrite (Angelico et al, 2014;Mikutta, 2011;Vilgé et al, 1999b).…”
Section: Introductionmentioning
confidence: 55%
“…This model of the structure of nanoCLICs differs from the models proposed in the literature. Previous models of coprecipitates included Fe only as ferrihydrite and monomeric Fe-OM (Eusterhues et al, 2014;Guenet et al, 2017;Kleber et al, 2015). In the model in Figure 6, other major elements potentially present in the soil solution are taken into account.…”
Section: Comparison With Previous Models and Limits Of The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the precipitation of Fe in the presence of OM constrains the particle size and structural order of Fe (Schwertmann et al, 2005;Eusterhues et al, 2008;Cismasu et al, 2011;Pédrot et al, 2011). These results in wider lattice spacing, fewer crystal planes and Fe monomers, polymers and nanoparticles bound to OM (Vilgé-Ritter et al, 1999;Guénet et al, 2017). Threlfall (2003) showed that clusters and nanoparticles grow through a continuous supply of Fe(III) and Waychunas et al, (2005) demonstrated that this occurs through particle and cluster aggregation as observed in Figure 5.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…following the procedure described in Guénet et al (2017). All references were measured in the same conditions as the samples.…”
Section: Accepted Manuscriptmentioning
confidence: 99%